PENGARUH KECUKUPAN MODAL, RISIKO KREDIT, LIKUIDITAS TERHADAP PROFITABILITAS PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Ika Fitriani Panjaitan; Hamonangan Siallagan; Jadongan Sijabat (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to examine the effect of capital adequacy, credit risk, liquidity on profitability. In this study, capital adequacy is measured by the Capital Adequacy Ratio (CAR), Credit risk is measured by Non Performing Loan (NPL), liquidity is measured by the Loan To Deposit Ratio (LDR). This type of research is Quantitative research. The population of banking sector companies listed on the Indonesia Stock Exchange for the period 2021-2023. The sampling process uses the purposive sampling method, the data analysis technique is carried out using multiple linear regression with the help of the SPSS version 26 program. The results of the study indicate that capital adequacy has a significant effect on profitability and liquidity has a significant effect on profitability while credit risk does not have a significant effect on profitability.